Enhanced hydrolysis and antitumor efficacy of Epimedium flavonoids mediated by immobilized snailase on silica. (November 2019) - Liu, Congyan; Li, Ruiyun; Peng, Jing; Qu, Ding; Huang, Mengmeng; Chen, Yan
Graphical abstract: Schematic illustration of efficient TEF hydrolysis and antitumor evaluation via immobilized snailase on SiO2 -NH2 -GA. Abstract: Enzyme immobilization on solid supports has great application potential in industry owing to the reusability, enhanced stability and easy product separation. In this study, immobilized snailase on glutaraldehyde-activated aminated silica (SiO2 -NH2 -GA) was prepared, characterized and applied to hydrolyze the epimedium flavonoids. The immobilized snailase had an enzymatic activity of 65.5 U under optimized condition when using icariin as substrate. Immobilization resulted in significant improvement of the pH tolerance, thermal tolerance and storage stability relative to the free snailase. The immobilized snailase could be reused for at least 6 times and retained more than 60% of the original activity. In addition, the immobilized snailase was applied to hydrolyze the total epimedium flavonoids (TEF) and the optimum hydrolysis conditions were investigated to obtain as much hydrolyzate as possible. Compared with TEF and the corresponding hydrolysate produced by free snailase, the hydrolysate produced by immobilized snailase exhibited significantly enhanced antiproliferative effect against A549, HepG2, Hela and MCF-7 cells, suggesting a better antitumor efficacy. In summary, our study shows that the immobilized snailase on functionalized silica could efficiently hydrolyze epimedium flavonoids to the hydrolysate with enhanced antitumor activity, providing a feasibility of green industrial production of active drugs in the future.